The VCDQ – a Questionnaire for symptom monitoring in vocal cord dysfunction. Issue 9 (September 2015) - Fowler, S. J.; Thurston, A.; Chesworth, B.; Cheng, V.; Constantinou, P.; Vyas, A.; Lillie, S.; Haines, J.
Summary Background Vocal cord dysfunction (VCD) typically involves abnormal adduction of the vocal cords during inspiration, mimics the symptoms of asthma and leads to the prescription of ineffective medications. Objective We aimed to develop a clinical tool to monitor symptoms and response to treatment in confirmed VCD. Methods We collated symptoms of VCD from focus groups comprising patients and healthcare professionals; phrases describing these symptoms were assessed for face validity and internal correlation and rated for importance. The resultant 12‐item questionnaire (VCDQ) rated the impact of each on a 5‐point Likert scale (total score range 12–60) and was tested for reliability, concurrent validity and performance in 31 patients with endoscopically confirmed VCD (± asthma), 29 asthmatics with no history of VCD and 14 healthy controls. We assessed response to speech and language therapy and the minimal important difference by measuring the VCDQ pre‐ and post‐ therapy in a 20 new patients. Results The VCDQ had excellent test–retest reliability and differentiated VCD vs. healthy (Mann–Whitney U‐test: z = −5.390, P < 0.001) and asthma (z = −5.730, P < 0.001). All patients improved post‐therapy, assessed both by a global rating of change score (GRCS) and by the VCDQ [median (IQR) score pre‐therapy 50.5 (48.0 – 54.8), post‐therapy 35.0 (29.3 – 41.8), P < 0.001]. The minimal important difference in the VCDQ associated with a rating of 'minimally better' on the GRCS was 4 points. Conclusions and Clinical Relevance The VCDQ is a valid and responsive tool suitable for measuring changes in symptoms in patients with VCD. It also gives insight into which symptoms are important to patients and could guide future therapy refinements. Future assessments of novel therapies for this condition should use an appropriately validated tool such as the VCDQ to measure response.